Exploring the Development of Geopolitical Studies: A Bibliometric Review of International Literature - Loso Judijanto (Jurnal Multidisiplin West Science, 2026)
In turn, the main purpose of this research is to analyze the development of the subject of geopolitics using a bibliometric analysis of the foreign scientific literature. It should be noted that a quantitative bibliometric method is used, based on publications on geopolitics, geopolitical risks, and political geography, data of which was taken from Scopus. Such bibliometric tools as co-authorship, citation, and keyword analyses will be carried out using the software program called VOSviewer, which will allow mapping collaboration, intellectual structure, and evolution of themes. The results show that geopolitics includes relatively fragmentary patterns of cooperation, but at the same time, there is a dominance of developed countries represented by the USA and European countries, along with an increase in the number of developing countries, such as China and India. As a result of the keyword analysis, one can notice a clear transition from topics related to traditional geopolitics and the power of states in international relations to multidisciplinary topics, such as energy security, climate change, geopolitical risks, and innovations. At the same time, overlay and density graphs indicate the temporal evolution of the topic, as well as an understanding of new priorities, such as sustainability, risk analysis, and digitalization.